Regulation of innate immune signaling by IRAK proteins - Pereira, Milton; Gazzinelli, Ricardo T. (Frontiers in Immunology, 2023)
The Toll-like Receptors (TLR) and Interleukin-1 Receptors (IL-1R) families are of paramount importance in coordinating the early immune response to pathogens. Signaling via most TLRs and IL-1Rs is mediated by the protein Myeloid Differentiation primary-response protein 88 (MyD88). This signaling adaptor forms the scaffold of the myddosome, a molecular platform that employs IL-1R-Associated Kinase (IRAK) proteins as main players for transducing signals. These kinases are essential in controlling gene transcription by regulating myddosome assembly, stability, activity and disassembly. Additionally, IRAKs play key roles in other biologically relevant responses such as inflammasome formation and immunometabolism. Here, we summarize some of the key aspects of IRAK biology in innate immunity.